Maternal antibiotics disrupt microbiome, behavior, and temperature regulation in unexposed infant mice. Issue 6 (19th June 2022) - Harshaw, Christopher; Kojima, Sayuri; Wellman, Cara L.; Demas, Gregory E.; Morrow, Ardythe L.; Taft, Diana Hazard; Kenkel, William M.; Leffel, Joseph K.; Alberts, Jeffrey R.
Abstract: Maternal antibiotic (ABx) exposure can significantly perturb the transfer of microbiota from mother to offspring, resulting in dysbiosis of potential relevance to neurodevelopmental disorders such as autism spectrum disorder (ASD). Studies in rodent models have found long‐term neurobehavioral effects in offspring of ABx‐treated dams, but ASD‐relevant behavior during the early preweaning period has thus far been neglected. Here, we exposed C57BL/6J mouse dams to ABx (5 mg/ml neomycin, 1.25 μg/ml pimaricin, .075% v/v acetic acid) dissolved in drinking water from gestational day 12 through offspring postnatal day 14. A number of ASD‐relevant behaviors were assayed in offspring, including ultrasonic vocalization (USV) production during maternal separation, group huddling in response to cold challenge, and olfactory‐guided home orientation. In addition, we obtained measures of thermoregulatory competence in pups during and following behavioral testing. We found a number of behavioral differences in offspring of ABx‐treated dams (e.g., modulation of USVs by pup weight, activity while huddling) and provide evidence that some of these behavioral effects can be related to thermoregulatory deficiencies, particularly at younger ages. Our results suggest not only that ABx can disrupt microbiomes, thermoregulation, and behavior, but that metabolic effects may confound the interpretation of behavioral differences observed after early‐life ABx exposure.